FAKTOR EMERGENCY CASE HIV AIDS DI BOJONEGORO - Susanti, Dwi Agung; Maftukhin, Ahmad; Afandi, Agus Ari (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2019)
ABSTRACT AIDS is a group of symptoms characterized by decreased immune system so that all infectious diseases are easy to attack, the cause is the Human Immunology Virus. Patients infected with HIV are considered to get a curse from God, so it is very disturbing psychological sufferers. Some are even ostracized, despised and ridiculed physically and mentally. From year to year HIV cases in Bojonegoro show an increase, HIV AIDS in Bojonegoro such as the